2002
DOI: 10.1161/01.atv.0000026298.00663.58
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Combined Blockade of ACE and AT 1 Receptor on Intimal Hyperplasia in Balloon-Injured Rat Artery

Abstract: Objective-The present study was undertaken to elucidate the effect of the ACE inhibitor and the angiotensin II type 1 (AT 1 ) receptor antagonist in combination on neointimal hyperplasia after balloon injury. Methods and Results-Temocapril (an ACE inhibitor), CS-866 (an AT 1 receptor antagonist), or their combination was given orally to rats, and their effects were compared on vascular hyperplasia induced by balloon injury. The maximal preventive effect of temocapril and CS-866 alone on neointimal thickening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…Kim et al have demonstrated that combination treatment with temocapril (an ACEI) and CS-866 (an ARB) prevented vascular smooth muscle cell proliferation in the intima to a greater extent than monotherapy in a rat balloon-injury model. They also demonstrated that L-NMMA, an NO synthase inhibitor, significantly attenuated the diminished intimal hyperplasia induced by combined administration of temocapril and CS-866 (34). Taking these findings together, one may speculate that the anti-atherosclerotic effect of the combination therapy in the present study was derived from the inhibition of NO synthesis.…”
Section: Discussionsupporting
confidence: 68%
“…Kim et al have demonstrated that combination treatment with temocapril (an ACEI) and CS-866 (an ARB) prevented vascular smooth muscle cell proliferation in the intima to a greater extent than monotherapy in a rat balloon-injury model. They also demonstrated that L-NMMA, an NO synthase inhibitor, significantly attenuated the diminished intimal hyperplasia induced by combined administration of temocapril and CS-866 (34). Taking these findings together, one may speculate that the anti-atherosclerotic effect of the combination therapy in the present study was derived from the inhibition of NO synthesis.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, the combination of an ACE inhibitor with an AT1R antagonist at maximally effective doses prevented structural and phenotypic changes to the vascular wall after balloon injury to a larger extent than single-site blockade. 43 …”
Section: Resultsmentioning
confidence: 99%
“…Kim et al reported that combination treatment with temocapril (an ACE inhibitor) and CS-866 (an AT1 receptor antagonist) along with blood pressure reduction prevent vascular smooth muscle cell proliferation in the intima to a greater extent than monotherapy with either agent and blood pressure reduction. They also demonstrated that L-NAME, an NO synthase inhibitor, significantly attenuated the diminished intimal hyperplasia induced by combined administration of temocapril and CS-866 (32). In another study, soluble guanylate cyclase α1 and β1 gene transfer to balloon-injured rat carotid arteries increased the NO responsiveness of vascular smooth muscle cells, and reduced neointima formation after balloon injury in rats (33).…”
Section: Fig 1 Systolic Blood Pressure (Sbpmentioning
confidence: 93%